ORAL SQUAMOUS CELL CARCINOMA IN A PATIENT WITH ORAL LICHENOID LESION (A CASE REPORT) - Nita Margaretha; Titiek Setyawati; Wirasmi Marwoto (Faculty of Dentistry, Universitas Indonesia, 2015)
Oral squamous cell carcinoma represents more than 90% of all oral cancers. Ten percent of the cases are found on the buccal mucosa and the gingiva. The World Health Organization defines a premalignant or precancerous lesion as a morphologically altered tissue in which cancer is most likely to occur and includes oral leukoplakia, oral erythroplakia, and possibly oral lichen planus (OLP). The purpose of this study was to discuss the possibility of malignant transformation of OLP. The potency of OLP as a premalignant lesion is still an ongoing controversial discussion in literature. The report a case of oral squamous cell carcinoma located on the left buccal mucosa accompanied by oral lichenoid lesions on the right buccal mucosa, lower labial mucosa, and left buccal mucosa. These findings led to a possibility of malignant transformation of the oral lichenoid lesion. Unfortunately, biopsy on the lichenoid lesions was not performed. Therefore, a definitive diagnosis of OLP could not be established and the possibility of the lesions being dysplastic remained unclear. This study concluded that biopsy is mandatory to establish a definitive diagnosis of OLP and to investigate the possibility of dysplasia. It is necessary to perform examination of genetic alteration in dysplastic OLP in order to assess loss of heterzygosity (LOH), which may help to consider the risk of malignant transformation.